Java Methods for Financial Engineering Applications in Finance and Investment - Barker, Philip (Springer London : Imprint: Springer, 2007)
This book is structured around the main theories and models used by practitioners to engineer finance and investment tools. The methods developed and implemented in the text are organized as chapters which cover the core areas. Each chapter is largely self-contained, thus the practitioner or student can conveniently focus on a defined tool and have immediate access to an implemented solution. Those engaged in the design and evaluation of new products will find the quick access to a wide range of robust core methods invaluable in constructing bespoke implementations. With the pervasiveness and rapid pace of advancement in Web based technologies, it is now a given that any commercially useful computational tool is able to make an effective and efficient use of Web based platforms. Java is the language of choice for developing highly efficient Web based applications. All of the methods in this book are written in Java and use is made of the fully optimised Java Collections for data manipulation. For practitioners and students alike who are still working with legacy C++ or Visual Basic implementations, this book will serve as an excellent reference for translating or porting their applications into a Web centric environment. Phil Barker followed an academic career for many years , holding a lectureship in Computer Science at Heriot-Watt University, Edinburgh where he led undergraduate degree and postgraduate master's courses in Computer Science and Accountancy. He has a considerable depth of commercial experience having directed research, technical and operations functions within technology based companies serving blue chips in finance, investment and banking. He is currently CEO of BWA Technologies Ltd a company specializing in the development of investment and risk management software.